Naloxone Prescribing Associated With Reduced Emergency Department Visits in the Military Health System. Issue 12 (17th December 2022) - Costantino, Ryan C.; Tilley, Laura C.; Gressler, Laura Elisabeth; Zarzabal, Lee Ann; Vasquez, Cynthia M.; Peters, Sidney; Pakieser, Jennifer; Highland, Krista B.; dosReis, Susan
Abstract : Purpose: The aim was to determine the association between the receipt of naloxone and emergency department (ED) visits within 60 days after the receipt of an opioid. Methods: A retrospective cohort of individuals 18 years of age or above, enrolled in TRICARE, and were dispensed an opioid at any time from January 1, 2019, through September 30, 2020 was identified within the United States Military Health System. Individuals receiving naloxone within 5 days of the opioid dispensing date were propensity score matched with individuals receiving opioids only. A logistic regression was used to estimate the odds of an ED visit in the 60-day follow-up period after the index opioid dispense event among those co-dispensed naloxone and those receiving opioids only. Results: Of the 2, 136, 717 individuals who received an opioid prescription during the study period, 800, 071 (10.1%) met study inclusion criteria. Overall, 5096 (0.24%) of individuals who received an opioid prescription were co-dispensed naloxone. Following propensity score matching, those who received naloxone had a significantly lower odds of ED utilization in the 60 days after receiving an opioid prescription (odds ratio: 0.74, 95% CI: 0.68–0.80, P <0.001). Conclusion: This study highlights the importance of expanding access to naloxone in order to reduce ED utilization. Future research is needed to examine additional outcomes related to naloxone receipt and develop programs that make naloxone prescribing a routine practice.